Same and Other: from Plato to Kierkegaard. A reading of a metaphysical thesis in an existencial key - Binetti, María José; KRÁLIK, ROMAN; Tkáčová, Hedviga; Roubalova, Marie (Journal of Education Culture and Society, 2021)
Aim. In his Kierkegaardian studies Jean Wahl states that there is a fundamental convergence between Plato and Søren Kierkegaard focused on the notions of identity and difference. Wahl suggests a sort of transposition of platonic metaphysics into the sphere of personal subjectivity. This paper intends to explain this passage from the same to the other from Plato to Kierkegaard. Concept. The article explains the passage from the same to the other from Plato to Kierkegaard. In both authors, the categories of being or not being, identity and difference, unity and multiplicity, becoming and rest explain the dynamic nature of the real. Results and conclusion. In both authors, the categories mensioned above explain the dynamic nature of the real. But while Plato applies these categories to the inteligibile word, Kierkegaard applies them to individual freedom, which supports reality as a whole. Cognitive value. Both searches lead to a single speculative answer and culminate in the same metaphysical categorisation, which applies analogously to everything real. Indeed, being and non-being, identity and difference, oneness and otherness, rest and becoming, explain the dialectic, intensive and relational dynamism of entia. At the same time, they essentially determine the power of human existence, infinitely possible and forever depending on the absolute.